1999
DOI: 10.1046/j.1440-1622.1999.01578.x
|View full text |Cite
|
Sign up to set email alerts
|

Spray of Phospholipid Powder Reduces Peritoneal Adhesions in Rabbits

Abstract: A combination of DPPC and PG sprayed as a 'puff' intraperitoneally reduces experimentally induced peritoneal adhesions in rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Mixed efficacy in rat and rabbit models [219,263,264], [134,261,262,[265][266][267] Collagen inhibitors (N-(3,4-dimethoxycinnamoyl) anthranilic acid [Transilast])…”
Section: Efficacy Comparable To Seprafilm In Rat Model [51] Role Of Amentioning
confidence: 99%
“…Mixed efficacy in rat and rabbit models [219,263,264], [134,261,262,[265][266][267] Collagen inhibitors (N-(3,4-dimethoxycinnamoyl) anthranilic acid [Transilast])…”
Section: Efficacy Comparable To Seprafilm In Rat Model [51] Role Of Amentioning
confidence: 99%
“…Several studies have already shown that SAPL applied to biological surfaces in vivo significantly improves boundary lubrication (39,42,43). Importantly, SAPL has also been shown to significantly reduce peritoneal adhesions following surgery (22,44). There may be a role for SAPL therapy, containing predominantly unsaturated PCs, following pleural disease or intrathoracic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found surfactant in other parts of the body, including pleura (17), articular cartilage (18), tendon (19), gastric wall (12,20), eustachian tube (21), and peritoneum (22). The phospholipid composition at these sites, however, has been found to vary from surfactant collected from alveoli (12,21).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments in this field have been done in rats by using hyaluronate based bioresorbable membranes [57], hemostatic fleeces with a collagen matrix coated with fibrinogen and thrombin [58] or poly-ethylene glycol membranes [59]. Furthermore, peritoneal adhesions have been reduced by a peritoneal application of phospholipids in rats [60] or a peritoneal spray of phospholipids in rabbits [61]. Hence, a mixture of sialomucin and phospholipids injected into the pleural space might provide a more efficient and less invasive method to prevent pleural adhesion.…”
Section: Hystological Remarksmentioning
confidence: 99%